Legal Relations In Private International Law (Journal of Legal Studies, 2014)
International relations established between different categories of persons presuppose the existence of specific legal regulations, meant to secure legal order to this effect. Such international relations are expressed both in legal relations between states as subjects of public international law, and in relations between natural and legal persons pertaining to other states. In this article we presented a few general considerations regarding legal relations with foreign elements, established between natural and/or legal persons, as subjects of private law, as well as regulation methods for legal relations with a foreign element.